Approaches influencing the self-development of students in the credit-modular system - Kholmatov Shokirjon Solievich (Peerian Journals Publishing, 2022)
In this article, we consider the functional, systematizing and subject-targeted approaches that affect the development of the individual during self-study of students on a credit-modular system. At the same time, we will also focus on the pedagogical foundations of the process of selfstudy on a credit-modular system.
Keywords: Credit-modular system; self-study; functional approach